INTERVENSI PENDIDIKAN GIZI DALAM PROGRAM KELAS IBU-BALITA DAN PEMBERIAN ZAT GIZI MIKRO (TABURIA) TERHADAP PENINGKATAN STATUS GIZI ANAK BALITA GIZI BURUK USIA 25-60 BULAN - , Abdul Basit, dr. Madarina Julia, MPH, Ph.D, Sp.A(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Many programs have been implemented to prevent and overcome malnutrition in children under five. Yet, only a few of the programs focuses on investment value to improve quality of human resources. Investment in nutrition program such as nutrition education can increase income and minimize flaws in benefits of every value invested as much as USD 32.30 compared to program of food subsidy USD 0.90, extra food for children under five USD 1.40 and program of extra foods for school children USD 2.80. Micronutrient (taburia) supplementation brings positive effects to growth that leads to improved nutrition status of children under five. Objective: To identify difference of intervention on nutrition education in the program of class of mothers of children under five and micronutrient (taburia) supplementation to increase of nutrition status in malnourished children under five of age 25-60 months. Method: The study was experimental randomized controlled trial non blinded design carried out within 90 days in 2012. There were 2 groups of intervention, i.e. group I with nutrition education in class of mothers of children under five as many as 3 times and extra foods of biscuits 120 g/day within 90 days, group II was supplemented with micronutrient (taburia) 1 gram/2days and biscuits 120 g/day within 90 days. Samples 66 malnourished children under five confirmed through assessment of index weight/height taken through random allocation technique using random table. Assessment of nutrition intake (energy, protein, Vitamin A, Vitamin C, Fe and zinc) used interview method of multiple food recall 24 hours and nutrition status of children under five used anthropometric measurement. Data analyzed using univariate and bivariate technique. Result: There was significant difference between intervention in nutrition education and taburia supplementation to increase of nutrition status of children under five (z-score of index of weight/height) (p=0.04), weight change (p=0.04) and there was no significant difference in nutrition intake (p>0.05) and height change of malnourished children under five (p=0.07). Intervention of health education contributed to increase of nutrition status of children under five (z-score of index of weight/height) 1,20+0,63 SD, weight increase 1.22±0.62 kg and height increase 1.45±0.80 cm, whereas intervention of micronutrient supplementation contributed to increase of nutrition status children under five (z-score of index of weight/height) 0,84+0,75 SD, weight increase 0.88±0.72 kg and height 1.08±0.78 cm. Conclusion: Intervension of nutritional education was superior as compared with administration of taburia in improving nutritional status (z-score index for weight/height), body weight and height of malnourished children under five years old.